Cosmopolitanism, Consumer Ethnocentrism, Dan Relatif Product Quality Terhadap Preferensi Konsumen Generasi Y Produk Pakaian Merek Zara Di Surabaya - Lusmiati Djamuddin; Dhani Ichsanuddin Nur (Jurnal MEBIS (Manajemen dan Bisnis), 2017)
The various choices and brands of domestic products as well as the global products offered by manufacturers, provide different preferences to various consumers. The purpose of this study to determine the factors that affect the consumer preferences generation Y to the product brand clothing zara in surabaya. The variables used in this study are: cosmopolitanism, consumer ethnocentrism, relative product quality and consumer preferences generation Y. Measurements were made with Likert scale. The population in this study is the Y-generation consumers who have visited the clothing brand outlets in Surabaya. The analysis technique used is partial least square.The results of this study is that cosmopolitanism contributes to the relative product quality of brand products in Surabaya, the relative quality of products contributes to the Y generation consumer preferences in the zara brand clothing products in Surabaya, cosmopolitanism contributes to consumer ethnocentrism, consumer ethnocentrism contributes to consumer preferences Y generation on zara brand clothing products in Surabaya and cosmopolitanism does not contribute to the Y generation consumer preferences on Zara brand clothing products.